2017
DOI: 10.1016/j.cell.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Degradation of CTCF Decouples Local Insulation of Chromosome Domains from Genomic Compartmentalization

Abstract: Summary The molecular mechanisms underlying folding of mammalian chromosomes remain poorly understood. The transcription factor CTCF is a candidate regulator of chromosomal structure. Using the auxin-inducible degron system in mouse embryonic stem cells, we show that CTCF is absolutely and dose-dependently required for looping between CTCF target sites and insulation of topologically associating domains (TADs). Restoring CTCF reinstates proper architecture on altered chromosomes, indicating a powerful instruct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

185
1,816
10
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,467 publications
(2,017 citation statements)
references
References 101 publications
(151 reference statements)
185
1,816
10
6
Order By: Relevance
“…Insulation and directionality of the contact footprint of CTCF sites also disappear upon Nipbl deletion (Extended Data Figure 6). However, we observe no effect of Nipbl deletion on CTCF occupancy, demonstrating that the loss of TADs and CTCF contact in ΔNipbl is not due to loss or changes in CTCF occupancy (Extended Data Figure 3), This further strengthens the very distinct roles of CTCF and cohesin in shaping chromosome architecture 14,18 .…”
Section: Disappearance Of Tads and Peakssupporting
confidence: 68%
See 2 more Smart Citations
“…Insulation and directionality of the contact footprint of CTCF sites also disappear upon Nipbl deletion (Extended Data Figure 6). However, we observe no effect of Nipbl deletion on CTCF occupancy, demonstrating that the loss of TADs and CTCF contact in ΔNipbl is not due to loss or changes in CTCF occupancy (Extended Data Figure 3), This further strengthens the very distinct roles of CTCF and cohesin in shaping chromosome architecture 14,18 .…”
Section: Disappearance Of Tads and Peakssupporting
confidence: 68%
“…The fact that we observe no effect on activity marks indicates that cohesin and TADs do not play a role in the maintenance of epigenetic state, though this does not rule out possible roles in its establishment. A recent study has observed a similar preservation of epigenetic state upon CTCF depletion 18 .…”
Section: Enhanced and Finer Compartmentalizationmentioning
confidence: 56%
See 1 more Smart Citation
“…These technologies provided critical insights into key structural and functional components of three-dimensional chromatin organization such as i) A/B compartments (Lieberman-aiden et al 2009), also referred to as compartment domains (Rao et al 2017), which are closely associated with open and closed chromatin domains, respectively; ii) topologically associating domains (TADs) (Dixon et al 2012;Nora et al 2012;Sexton et al 2012), also referred to as contact domains (Rao et al 2017), chromosomal units that spatially constrain cis-regulatory interactions; iii) CTCF loops, also referred to as insulated neighborhoods (Hnisz et al 2016) or loop domains (Rao et al 2017). Interestingly, while these studies suggested a hierarchical domain organization, recent studies based on acute depletion of CTCF or cohesin, or inactivation of the cohesin-loading factor NIPBL, demonstrated that A/B compartments and TADs are not hierarchically organized but represent independent structural (and possibly functional) units of 3D genome organization (Nora et al 2017;Rao et al 2017;Wutz et al 2017;Schwarzer et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…These differences imply that the three levels of organization might have distinct origins and roles. This idea is supported by the fact that experimental depletion of different chromatin-associated proteins can have differential effects on each feature [8][9][10][11] . In addition, a recent Hi-C analysis 12 of the 4 investigate changes in folding of the DNA-RNA-protein complex chromatin during mitotic cell divisions and during interphase, the period between divisions when DNA replication occurs.…”
mentioning
confidence: 52%